Competition matters: using in vitro community models to study the impact of human skin bacteria on mosquito attraction - Lucas-Barbosa, Dani; Balvers, Carlijn; Bellantuono, Anthony J.; Castillo, John S.; Costa-da-Silva, André L.; De Moraes, Consuelo M.; DeGennaro, Matthew; Verhulst, Niels O. (Frontiers in Ecology and Evolution, 2023)
The human skin bacteria play an important role in the production of volatiles that attract mosquitoes. Using some of the most abundant human skin bacterial species, we created in vitro community models to assess whether increased microbial biodiversity could reduce human attractiveness to females of the dengue fever mosquito Aedes aegypti and whether co-culturing bacterial commensals affects overall attraction. More complex bacterial models were less attractive to female mosquitoes than the simplest models. For instance, the triple bacterial community model was approximately three times less attractive than Staphylococcus epidermidis alone. Our data shows, for instance, that an in vitro community model mimicking the skin composition of a highly attractive individual to the anthropophilic Anopheles gambiae was also more attractive to anthropophilic Ae. aegypti than a community model mimicking the skin composition of a poorly attractive individual to An. gambiae. In line with these results, volatile analyses of the blends emitted by the different in vitro community models showed that the more complex models had lower emission overall. Effects on mosquito responses differed sharply when the different bacteria species were sharing the same resources used for growth, showing that either competition or commensalism may influence their relative growth, and that this consequently can influence mosquito responses. We conclude that studies on mosquito responses to skin volatiles need to take the microbial community into account.